2022
DOI: 10.1155/2022/4688312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Levels of Dietary Emamectin Benzoate on Immunity, Enzyme Activity, and Withdrawal Period in Labeo rohita Juveniles (Hamilton, 1822)

Abstract: This study was conducted to evaluate the effect of dietary emamectin benzoate (EB) levels on immune responses, serum enzyme activities, and retention of EB in muscle tissue to establish the withdrawal period in rohu, Labeo rohita juveniles (avg. wt. 18 ± 0.11  g). To ascertain this, 450 healthy L. rohita juveniles were fed with EB in graded doses viz., at 50 (1x), 125 (2.5x), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(44 reference statements)
2
4
0
Order By: Relevance
“…Even a slight appetite decrease in fish treated with 5× and 10× EB doses did not affect the growth of the golden mahseer juveniles. This finding is supported by similar studies, where the growth of fish were not affected when administered with higher EB doses through medicated feed (Julinta et al, 2020;Raja et al, 2020;Choudhary et al, 2022). Also, the toxicity study in Atlantic salmon and rainbow trout corroborate our finding, where the growth of EB treated fish were not affected as compared to control one fed with EBfree diet (Roy et al, 2000;Bowker et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Even a slight appetite decrease in fish treated with 5× and 10× EB doses did not affect the growth of the golden mahseer juveniles. This finding is supported by similar studies, where the growth of fish were not affected when administered with higher EB doses through medicated feed (Julinta et al, 2020;Raja et al, 2020;Choudhary et al, 2022). Also, the toxicity study in Atlantic salmon and rainbow trout corroborate our finding, where the growth of EB treated fish were not affected as compared to control one fed with EBfree diet (Roy et al, 2000;Bowker et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Here, we concluded that EB residue in muscle is within the MRL, even if it is administered for three times the recommended duration of 7 consecutive days at dose of 50 μg/kg fish/day. Similar research has been conducted in different fishes from different geographical locations of the world, where adequate margin of safety of EB was reported at recommended dose (Kim-Kang et al, 2004;Whyte et al, 2011;Collymore et al, 2014;Neto et al, 2019;Julinta et al, 2020;Raja et al, 2020;Choudhary et al, 2022). In our study, the traces of Emamectin B 1a were still detected in muscle tissues of EB treated golden mahseer after 30 days post-medication, which suggests the complete withdrawal of EB require more than 30 days in golden mahseer.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The decreased activity of alkaline phosphatase in pesticide-exposed fish may be connected to the interactions between pesticides and co-factors and regulators, as well as its inducement to cell organelle damage such as the endoplasmic reticulum and membrane transport system damage (Al-Ghanim et al 2020 ). On the contrary, the Labeo rohita juveniles fed with emamectin benzoate ≥ 250 μg kg −1 of fish biomass per day for 21 days had considerably high levels of ALP (Choudhary et al 2022 ). The marked increase in serum total protein, albumin, and globulin was recorded in O. niloticus exposed to ABM acute toxicity at 5 µg/l for 96 h (Farag and Reda 2021 ).…”
Section: Discussionmentioning
confidence: 99%